PELAKSANAAN TUGAS POKOK DAN FUNGSI KANTOR WILAYAH HUKUM DAN HAM RIAU DALAM PEMBINAAN WARGA BINAAN LEMBAGA PEMASYARAKATAN KELAS IIA BENGKALIS - Ryan Pratama; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The increase in crimes that often occur in the community has caused prison sentences to soar, resulting in overcapacity. The Riau Province Regional Office of Law and Human Rights has the main tasks and functions in carrying out legal services throughout the territory of Riau Province. One of them is coaching inmates at the Bengkalis Class IIA Penitentiary. Less than optimal coaching can result in prisoners not getting the purpose of the correctional system so that they have the potential to recidivate after being released from their punishment period. There are several obstacles that result in the coaching carried out at the Bengkalis Class IIA Penitentiary not running smoothly. There needs to be an effort by the Riau Regional Office of Law and Human Rights in coaching activities and overcoming the problem of overcapacity at the Bengkalis Class IIA Penitentiary. This study aims to determine the implementation of the main tasks and functions carried out by the Riau Regional Office of Law and Human Rights in providing guidance to prisoners at the Bengkalis Class IIA Penitentiary. This research method uses a qualitative approach with descriptive research type. The research location was at the Riau Regional Office of Law and Human Rights and the Bengkalis Class IIA Penitentiary. The data collection techniques used were interviews and documentation. The results showed that implementation of the Mandate and Function of Riau Regional Office of Law and Human Rights in rehabilitating is monitoring and evaluation. It aims to analyze all coaching activities at the Bengkalis Class IIA Penitentiary which is given the freedom to plan and carry out rehabilitation according the talents and interests of inmates. Development activities are carried out based on indicators of the success of improving the quality of individual prisoners. However, the implementation of coaching has not optimally because several obstacles. Obstacles such as overcapacity, quality and quantity of officers, limited facilities and limited participation in the rehabilitation activity. Keywords: Mandate and Functions, Rehabilitation, Inmates